A new model of regression rate for solid fuel scramjet. (December 2019) - Zhang, Hao; Wang, Ningfei; Wu, Zhiwen; Han, Wanzhi; Du, Rui
Highlight: The model overcomes the limitations of using the Nusselt number to calculate heat flux. The model can also be used to obtain the regression rate in hybrid rocket and ramjet. The model has been verified by experiments. Abstract: A new theoretical model has been developed to calculate the regression rate of solid fuel scramjet (SF-Scramjet). This model obtains the local regression rate by calculating the local heat flux on the fuel surface, which is obtained by a standard wall function. A two-dimensional, axisymmetric, turbulent, one-reaction model which used the new method was developed to study the solid fuel regression rate for SF-Scramjet numerically with a flight environment of 25 km and a Mach number of 6. The quasi-steady state numerical method has been adopted to calculate the regression rate at different times. Experiments were carried out on the ground dedicated connected-pipe static test facility under the same boundary conditions to verify the correctness of the model. The results demonstrate that the numerical results agree well with the experimental results in the first few seconds. In the next few seconds of combustion, the numerical results of the regression rate gradually deviate from the experimental results. This may be due to the gradual accumulation of errors in the quasi-steady method.